2021
DOI: 10.3389/fimmu.2021.625957
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Attenuates Endotoxin-Induced Lung Injury by Activating Thioredoxin 1 and Decreasing Tissue Factor Expression

Abstract: Endotoxin-induced lung injury is one of the major causes of death induced by endotoxemia, however, few effective therapeutic options exist. Hydrogen inhalation has recently been shown to be an effective treatment for inflammatory lung injury, but the underlying mechanism is unknown. In the current study we aim to investigate how hydrogen attenuates endotoxin-induced lung injury and provide reference values for the clinical application of hydrogen. LPS was used to establish an endotoxin-induced lung injury mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It inhibits NF-κB signaling pathway-mediated inflammation and apoptosis in the lung (Xie et al 2012), reduces p38 MAPK expression and inhibits p38 MAPK activation (Liang et al 2012), inhibits the RhoA mediated pathway (Yang et al 2016), and modulates autophagy through the mTOR/TFEB signaling pathway and the PINK1/Parkin mitophagy pathway (Fu et al 2020;Chen et al 2021). Recently, molecular hydrogen was found to activate thioredoxin 1 and decrease tissue factor expression, alleviating inflammatory and coagulation cascade reactions (Li et al 2021). Through these mechanisms, molecular hydrogen considerably improved the survival rate of mice with LPS and reduced lung edema and hemorrhage, inflammatory cell infiltration, and inflammatory cytokine secretion.…”
Section: Sepsis-induced Alimentioning
confidence: 99%
See 1 more Smart Citation
“…It inhibits NF-κB signaling pathway-mediated inflammation and apoptosis in the lung (Xie et al 2012), reduces p38 MAPK expression and inhibits p38 MAPK activation (Liang et al 2012), inhibits the RhoA mediated pathway (Yang et al 2016), and modulates autophagy through the mTOR/TFEB signaling pathway and the PINK1/Parkin mitophagy pathway (Fu et al 2020;Chen et al 2021). Recently, molecular hydrogen was found to activate thioredoxin 1 and decrease tissue factor expression, alleviating inflammatory and coagulation cascade reactions (Li et al 2021). Through these mechanisms, molecular hydrogen considerably improved the survival rate of mice with LPS and reduced lung edema and hemorrhage, inflammatory cell infiltration, and inflammatory cytokine secretion.…”
Section: Sepsis-induced Alimentioning
confidence: 99%
“…activating Nrf2/HO-1; improves mitochondrial function; decreases NLRP3 inflammasome through activating autophagy Inhibits NF-κB; inhibits p38 MAPK; inhibits RhoA; modulates mTOR/TFEB autophagy and PINK1/Parkin mitophagy; activates thioredoxin 1 and decreases tissue factor expressionXie et al (2010Xie et al ( , 2012,Liang et al (2012),Li et al (2015Li et al ( , 2021,Yang et al (2016),Dong et al (2018),Chen et al (2019Chen et al ( , 2021, Yu et al (2019), Fu et al (2020) COVID-19 Inhibits MCP-1, IL-6, IL-1β; inhibits NLRP3 pathway, modulates Nrf2 signaling pathway Chen et al (2019), Niu et al (2020), Wang et al (2020) I/R induced ALI Induces HO-1, inhibits p38 MAPK and NF-κB, decreases IL-8, IL-1β, TNF-α; inhibits apoptosis and pyroptosis Kawamura et al (2010, 2011), Liu et al (2015b), Zhang et al (2018), Saito et al (2020), Zheng et al (2021a) HILI Activates Nrf2/HO-1; increases SIRT1; protects AECIIs by modulating related proteins expression and biological processes Kawamura et al (2013), Sun et al (2017), Lu et al (2018) VILI Reduces inflammatory responses at local and systemic level; increases the early activation of NF-κB Huang et al (2010, 2011) Irradiation-induced lung injury Reduces ROS and apoptosis in A549 cells; reduces lung fibrosis Terasaki et al (2011) Burn induced ALI Attenuates oxidative stress and inflammation; may modulate SIRT1 Fang et al (2011), Bai et al (2015), Qin et al (2017) ALI induced by other causes The protective effects are mainly by inhibiting oxidative stress, inflammation, apoptosis Diao et al (2016), Hong et al (2016), Ying et al (2017),Terasaki et al (2019) …”
mentioning
confidence: 99%
“…Neutrophils are great producers of ROS and play a role in ageing [ 44 ]. H 2 reduces neutrophil infiltration in the injured tissue [ 45 ], potentially decreasing the generation of ROS. MPO is a heme-containing peroxidase that is mainly expressed in neutrophils.…”
Section: Potential Mechanisms Of Molecular H 2 Act...mentioning
confidence: 99%
“…Our previous studies have shown that hydrogen (H 2 ) alleviates lung injury during sepsis by upregulating Trx1 [16]. H 2 has also been reported to inhibit MMP-9 activity in order to reduce brain infarction and improve neurological function [17].…”
Section: Introductionmentioning
confidence: 99%